2016
DOI: 10.5897/ajmr2015.7760
|View full text |Cite
|
Sign up to set email alerts
|

Biopeptides with antioxidant activity extracted from the biomass of Spirulina sp. LEB 18

Abstract: The microalga Spirulina has been marketed in many countries due to its application in foods, especially for its high protein content, which can be used to obtain protein hydrolysates. Protein hydrolysates are easily absorbed by the gastrointestinal tract and have significant physiological properties, because during the hydrolysis process, peptides with antioxidant activity can be obtained. The objective of this study was to obtain enzymatic hydrolysates from the biomass of Spirulina sp. LEB 18 with functional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 38 publications
0
4
0
3
Order By: Relevance
“…De acordo com Souza (2012), os dados obtidos permitem afirmar que as microalgas estudadas são basicamente constituídas por proteínas e hidratos de carbono. Lisboa et al (2016), confirmam, em seu trabalho com hidrolisados proteico, que a biomassa de Spirulina sp. LEB 18 tem uma alta concentração de proteína e as condições requeridas para crescimento podem ser alteradas para estimular uma concentração mais elevada deste bioproduto, a concentração obtida por estes autores foi 51.66%, semelhante a este estudo (Quadro 1).…”
Section: Composição Proximal E Digestibilidade In Vitrounclassified
See 1 more Smart Citation
“…De acordo com Souza (2012), os dados obtidos permitem afirmar que as microalgas estudadas são basicamente constituídas por proteínas e hidratos de carbono. Lisboa et al (2016), confirmam, em seu trabalho com hidrolisados proteico, que a biomassa de Spirulina sp. LEB 18 tem uma alta concentração de proteína e as condições requeridas para crescimento podem ser alteradas para estimular uma concentração mais elevada deste bioproduto, a concentração obtida por estes autores foi 51.66%, semelhante a este estudo (Quadro 1).…”
Section: Composição Proximal E Digestibilidade In Vitrounclassified
“…(Rodrigues, 2008;Lisboa et al, 2016). As espécies Spirulina platensis e Spirulina máxima são as mais estudadas para uso na alimentação humana por apresentarem um perfil nutricional que as torna ideais como suplemento alimentar, pois substituem satisfatoriamente as fontes artificiais de nutrientes, por combinar diversos constituintes de maneira equilibrada.…”
Section: Perfil De Aminoácidos Das Microalgasunclassified
“…It is know that Cyanobacteria can stimulate plant metabolism through their bioactive compounds and thus promote plant growth [35]. Among the reported potential bioactive compounds found in these organisms, as hormones [6], polyamines [13] and amino acids [10], being the last one found at high amount in…”
Section: Resultsmentioning
confidence: 99%
“…The presence of phytohormones as auxins, gibberellins, cytokinins and abscisic acid inside this cyanobacterial cells or exogenously released by them, with potential plant growth promotion effect are being documented [9]. The A. platensis composition also presents high levels of L-amino acids [10] around 58% of their total protein content [11], which also may help in plant growth [12]. It was reported that one of the bioactive molecules on A. platensis is their polyamine content, mainly spermidine, which biosynthesis depends on L-amino acids and could stimulate cell multiplication and plant growth [13].…”
Section: Introductionmentioning
confidence: 99%
“…These biocomposites contain from 3 to 20 amino acids residues and are formed from hydrolysis of the microalgal biomass as they are inactive within the protein sequence. The hydrolysis of the proteins improves the digestibility of the microalgal biomass, since molecules of lower molecular weight are obtained and are more easily absorbed by the organism (Lisboa et al, 2016).…”
Section: Characterization Of Biomass Composition Centesimal Compositionmentioning
confidence: 99%